Clinical, Immunological, and Virological SARS-CoV-2 Phenotypes in Obese and Nonobese Military Health System Beneficiaries. (31st July 2021) - Epsi, Nusrat J; Richard, Stephanie A; Laing, Eric D; Fries, Anthony C; Millar, Eugene; Simons, Mark P; English, Caroline; Colombo, Christopher J; Colombo, Rhonda E; Lindholm, David A; Ganesan, Anuradha; Maves, Ryan C; et al.
Abstract : Obesity is correlated with COVID-19 severity, SARS-CoV-2 viral load, and anti-spike IgG antibody responses. These findings offer new pathophysiological insights into the relationship between obesity and COVID-19 severity. Abstract: Background: The mechanisms underlying the association between obesity and coronavirus disease 2019 (COVID-19) severity remain unclear. After verifying that obesity was a correlate of severe COVID-19 in US Military Health System (MHS) beneficiaries, we compared immunological and virological phenotypes of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection in both obese and nonobese participants. Methods: COVID-19–infected MHS beneficiaries were enrolled, and anthropometric, clinical, and demographic data were collected. We compared the SARS-CoV-2 peak IgG humoral response and reverse-transcription polymerase chain reaction viral load in obese and nonobese patients, stratified by hospitalization, utilizing logistic regression models. Results: Data from 511 COVID-19 patients were analyzed, among whom 24% were obese and 14% severely obese. Obesity was independently associated with hospitalization (adjusted odds ratio [aOR], 1.91; 95% confidence interval [CI], 1.15–3.18) and need for oxygen therapy (aOR, 3.39; 95% CI, 1.61–7.11). In outpatients, severely obese had a log10 (1.89) higher nucleocapsid (N1) genome equivalents (GE)/reaction and log10 (2.62) higher N2 GE/reaction than nonobese ( P = 0.03 and P < .001, respectively). We noted a correlation between body mass index and peak anti-spike protein IgG in inpatients and outpatients (coefficient = 5.48, P < .001). Conclusions: Obesity is a strong correlate of COVID-19 severity in MHS beneficiaries. These findings offer new pathophysiological insights into the relationship between obesity and COVID-19 severity.